Pentraxin 3: An Immuno-Regulator in the Lungs - Balhara, Jyoti; Koussih, Latifa; Zhang, Jingbo; Gounni, Abdelilah S. (Frontiers in Immunology, 2013)
Pentraxin-3 (PTX3), is a soluble pattern recognition receptor (PRR) and constitutes humoral component of the innate immune system. It interacts with pathogenic moieties, infected and dying host cells and facilitates their removal through activation of appropriate innate and adaptive mechanisms. PTX3 is secreted by a diverse variety of cells, ranging from immune cells to structural cells, in response to toll like receptor (TLR) engagement, inflammatory stimuli, physical and chemical stress. Further, PTX3 plays an essential role in female fertility as it facilitates the organization of extracellular matrix in cumulus oophorus. Such activity is also implicated in post-inflammation tissue repair. Altogether, PTX3 is a multifunctional protein and plays a non-redundant role in providing immunity against potential immunological dangers. Hence, it would be noteworthy to assess its role in lung immunity, as lungs are at a constant risk of infections and tissue damage attributable to perpetual exposure to foreign agents in air.